2020
DOI: 10.1093/mnrasl/slaa114
|View full text |Cite
|
Sign up to set email alerts
|

Theory of ion holes in space and astrophysical plasmas

Abstract: ABSTRACT Coherent bipolar electric field structures, ubiquitously found in various space and astrophysical plasma environments, play an important role in plasma transport and particle acceleration. Most of the studies found in the literature about them pertain to bipolar structures with positive potentials interpreted in terms of electron holes. Magnetospheric Multiscale spacecraft have recently observed a series of coherent electric field structures with negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Figure 1 represents the case when the temperature ratio is 0.5 and Figure 2 represents the case when the temperature ratio is 3. It is interesting to note that for a vanishing value of the Havnes parameter that is in the limit H = 0, our theoretical results essentially recover the results of Aravindakshan et al (2020Aravindakshan et al ( , 2021. Figure 1 (bottom right panel) and Figure 3 depict the width-amplitude relation for ion holes generated in an electron-ion (i.e., nondusty) plasma (H = 0) for temperature ratios 0.5 and 3, respectively.…”
Section: Parametric Analysis and Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Figure 1 represents the case when the temperature ratio is 0.5 and Figure 2 represents the case when the temperature ratio is 3. It is interesting to note that for a vanishing value of the Havnes parameter that is in the limit H = 0, our theoretical results essentially recover the results of Aravindakshan et al (2020Aravindakshan et al ( , 2021. Figure 1 (bottom right panel) and Figure 3 depict the width-amplitude relation for ion holes generated in an electron-ion (i.e., nondusty) plasma (H = 0) for temperature ratios 0.5 and 3, respectively.…”
Section: Parametric Analysis and Discussionsupporting
confidence: 66%
“…Figure 3. The width-amplitude plot is shown in the case where the Havnes parameter is kept at H = 0, i.e., in the absence of dust (electron-ion plasma), as depicted in the ion-hole theory developed by Aravindakshan et al (2020) while taking T r = 3, considering various kappa index values. Here κ e and κ i denote the superthermal indices of electrons and ions, respectively.…”
Section: Theoretical Modelingmentioning
confidence: 99%
“…In earlier theoretical studies, it has been shown that the generation of ion holes is limited to the plasmas having Ti/Te < 0.3 (Schamel 1982). However, a recently developed theoretical model supports the generation of ion holes for T i /T e > 0.3 as well (Aravindakshan et al 2020). The generation of ion holes in such plasmas is reported by Wang et al (2020), where Ti/ Te∼ 0.4.…”
Section: Discussionmentioning
confidence: 97%
“…This could be a possible reason for getting f pi f ef < <f pe for observed electric field pulses. These ion-acoustic type solitary waves can have different generation mechanisms, e.g., they can be ion-acoustic solitary waves (Kakad et al 2013) or ion holes (Akimoto & Winske 1985;Aravindakshan et al 2020) driven by an ionbeam instability. In order to look into their possible generation mechanisms, we performed a fluid simulation, which is discussed in the next subsections.…”
Section: Characteristics Of Solitary Pulsesmentioning
confidence: 99%
“…non-Maxwellian background plasma. This was already pointed out in (Schamel , 2015(Schamel , , 2023 and carried out in (Haas , 2021;Aravindakshan , 2018Aravindakshan , , 2020Jenab , 2021). In (Haas , 2021) the Maxwellian description of the trapped (hole) and untrapped (background) electron populations was substituted by one with a so-called standard kappa distribution (SKD).…”
Section: Introductionmentioning
confidence: 99%